Lignan Biosynthesis Enhancement in Transgenic Wheat - Ayella, Allan K.; Wang, Weiqun (Nova Science Publishers, 2011)
Phytochemical lignans are phenylpropane dimers linked by β-β bonds with a 1,4- diarylbutane structure. They are biosynthesized in the cell cytoplasm through action of enzymes of the phenylpropanoid pathway, in which phenylalanine ammonia lyase (PAL) catalyzes the initial step of the secondary metabolism and pinoresinol laciresinol reductases (PLR) accelerates the final steps of biosynthesis of lignans. Lignans not only present abundantly in flaxseed but also in various grains such as wheat. Epidemiological and clinical studies have shown a correlation between the consumption of lignan-rich whole grain products and a reduced cancer risk. In animal models, lignans have been shown to have cancer preventive activities. Our previous studies demonstrated that the contents in lignans in various wheat cultivars were significantly associated with antitumor activities in APCmin mice. This review article covers updated aspect of lignans with emphasis on our recent lignan biosynthesis enhancement via transgenic engineering in wheat by over-expressing PLR gene. To develop a stably expression and more efficient transformation, a future study in genetically engineered wheat with pathway transformation by over-expressing both the PAL and PLR enzymes will be further discussed.
Keywords: Lignans; Wheat; Transgenic engineering; Biosynthesis